2019
DOI: 10.1093/cid/ciz1202
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin Can Be Given as Flat-Dosing Instead of Weight-Band Dosing

Abstract: Background The weight-band dosing in tuberculosis treatment regimen has been implemented in clinical practice for decades. Patients will receive different number of fixed dose combination tablets according to their weight-band. However, some analysis has shown that weight was not the best covariate to explain variability of rifampicin exposure. Furthermore, the rationale for using weight-band dosing instead of flat-dosing becomes questionable. Therefore, this study aimed to compare the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In patients who are greater than 10% below ideal body weight, clinicians may need to prolong treatment if there is delayed mycobacterial eradication or clinical evidence of poor treatment response. However, some studies have suggested that dosing adjustments for low body weight leads to low plasma drug levels and treatment inefficacy, particularly for rifamycin drugs [60] , [61] . Clinicians must balance the risk of adverse effects with the danger of treatment failure.…”
Section: Anti-tuberculosis Treatment In Older Adultsmentioning
confidence: 99%
“…In patients who are greater than 10% below ideal body weight, clinicians may need to prolong treatment if there is delayed mycobacterial eradication or clinical evidence of poor treatment response. However, some studies have suggested that dosing adjustments for low body weight leads to low plasma drug levels and treatment inefficacy, particularly for rifamycin drugs [60] , [61] . Clinicians must balance the risk of adverse effects with the danger of treatment failure.…”
Section: Anti-tuberculosis Treatment In Older Adultsmentioning
confidence: 99%
“…A total of 19 studies, of which 16 involved adults, 19,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] two involved children 50,51 and one involved both adults and children, were included in the review. 47 Six studies were conducted in South Africa, 31,32,52,53,54,55 two in China, 36,43 Mexico, 37,56 South Korea 30,39 and Uganda, 19,49 and one each in Japan, 35 Ghana, 46 Malawi, 47 Singapore 40 and Tanzania. 38 Overall, the number of subjects who participated in the included studies ranged from 25 to 261, while the total number of blood samples ranged between 95 and 2913.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition, there is a moderate IIV (IIV in AUC 0-24h of 25.4%) (Al-Sallami et al, 2014), and high IOV (IOV in AUC 0-24h of 25.8%) in the PK, which creates difficulties in performing individual dosing. Rifampicin IIV leads to variation in exposure between patients given the same dose, even if weight-based dosing is used (Susanto et al, 2019). While some of the variability between patients can be explained with patient characteristics such as HIV co-infection or sex (McIlleron et al, 2006), differences in drug formulations (McIlleron et al, 2006), pharmacogenetic factors (Weiner et al, 2010;Chigutsa et al, 2011), and variability in drug absorption, depending on concomitant food intake (Polasa and Krishnaswamy, 1983;Zent and Smith, 1995;Peloquin et al, 1999), some remain unexplained and are expressed as IIV.…”
Section: Introductionmentioning
confidence: 99%